2021
DOI: 10.21203/rs.3.rs-957738/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Association Between Neuroticism and Premenstrual Syndrome Symptoms.

Abstract: Background and objectives: Premenstrual syndrome includes physical and mental symptoms occurring cyclically during the secretory phase. The present study aimed to specify the association between neuroticism and the severity of premenstrual syndrome symptoms. Method: This cross-sectional study was conducted on 223 students of Kerman University of Medical Sciences in 2019 November 17. Chi-square and Fisher’s exact tests were used to analyze the relationship between qualitative variables; stepwise logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The results of regression analysis showed that neuroticism and stress were positively correlated with PMS, which corresponded with prior research [54,[69][70][71]. The more neurotic an individual is, the more likely they are to experience PMS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of regression analysis showed that neuroticism and stress were positively correlated with PMS, which corresponded with prior research [54,[69][70][71]. The more neurotic an individual is, the more likely they are to experience PMS.…”
Section: Discussionsupporting
confidence: 87%
“…The more neurotic an individual is, the more likely they are to experience PMS. Neuroticism is the personality trait that refers to the tendency to be emotionally sensitive, moody, easily anxious, depressed, overly worried, and susceptible to negative emotions [54,69,70]. Higher levels of neuroticism are associated with more negative moods in daily life and more life stress [70], which may lead to more negative responses to premenstrual physical symptoms and attitudes toward menstruation, higher perceived depression and stress, and more PMS.…”
Section: Discussionmentioning
confidence: 99%